Proceedings of the 2016 International Conference on Biomedical and Biological Engineering 2016
DOI: 10.2991/bbe-16.2016.65
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone Stress on Secondary Metabolism and Antioxidant Capacity in Soybean Roots

Abstract: In this paper, to examine the effects of elevated ozone on secondary metabolism and antioxidant capacity in soybean roots, as well as reactive oxygen species and antioxidant enzymes activity. Soybean grown in open top chambers (OTCs) were exposed to ambient air ([O 3 ]=40nmol•mol-1) and elevated ozone ([O 3 ]=110±10nmol•mol-1). The results revealed that with ozone concentration rising, compared with control, the O 3 stress induced the total flavonoids content in soybean root of all treatments showed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…In this study, we found that O 2 •production rate in potato tubers inoculated with ozonetreated F. sulphureum was higher than that of the control group, and a similar trend was found in H 2 O 2 content (Figure 3), indicating that ozone treatment activated ROS metabolism through increasing O 2 •production rate and H 2 O 2 accumulation. These findings are consistent with the report of Zhao et al [31], who suggested that ozonetreated soybean roots led to higher O 2 •production rate and H 2 O 2 content than the control group, which was ascribed to ozone-induced oxidative stress. O 2 •mainly comes from NOX that can reduce oxygen molecules into superoxide anion through NADPH-dependent single electron reduction, thereby regulating the production of superoxide anion, which is the main source of ROS in the cell and the only enzyme that directly produces ROS in the cell [18].…”
Section: Ozone Treatment Maintained Cell Membrane Integrity By Activa...supporting
confidence: 93%
“…In this study, we found that O 2 •production rate in potato tubers inoculated with ozonetreated F. sulphureum was higher than that of the control group, and a similar trend was found in H 2 O 2 content (Figure 3), indicating that ozone treatment activated ROS metabolism through increasing O 2 •production rate and H 2 O 2 accumulation. These findings are consistent with the report of Zhao et al [31], who suggested that ozonetreated soybean roots led to higher O 2 •production rate and H 2 O 2 content than the control group, which was ascribed to ozone-induced oxidative stress. O 2 •mainly comes from NOX that can reduce oxygen molecules into superoxide anion through NADPH-dependent single electron reduction, thereby regulating the production of superoxide anion, which is the main source of ROS in the cell and the only enzyme that directly produces ROS in the cell [18].…”
Section: Ozone Treatment Maintained Cell Membrane Integrity By Activa...supporting
confidence: 93%